Rhizobium inoculation sustains optimal yields on native common bean (Phaseolus vulgaris L.) under nitrogen-deficient fertilization - Vásquez Lozano, Danny Jarlis (2025)
Native bean genotypes (Phaseolus vulgaris L.) play a crucial role in ensuring food security in the Andean region. However, their cultivation faces challenges, such as low yields and a high dependence on nitrogen fertilizers. Addressing these issues requires the development of sustainable strategies to enhance productivity. This study evaluated the interaction between Rhizobium phaseoli inoculation and three levels of phosphorus (P) and potassium (K) fertilization on the growth, yield, and nutritional profile of the 'Tiachos bayo' native bean variety under Andean field conditions. Two R. phaseoli strains (UNC-1 and CIAT-2) were tested in combination with three levels of chemical fertilization (0%, 50%, and 100%) using a factorial design under field conditions. Parameters assessed included nodule number, plant height, phenology, yield, and proximal grain composition. Results indicated that inoculation and fertilization levels significantly influenced nodulation, phenological phases, and crop yield. The highest yield (2172 kg·ha⁻¹) and nodule number (78) were observed with the combined treatment of R. phaseoli CIAT-2 strain with 100% fertilization. It was concluded that R. phaseoli inoculation, when integrated with appropriate fertilization, enhances the productivity of native beans.